Optimization of load-bearing structures with respect to environmental impact: An implementation of an optimization tool for timber industrial buildings in early design stages based on parametric design - Elm Dahlman, Wilma; Tynelius, Hanna (My University, 2023)
The Swedish government has set up national goals to reach net zero emissions from human activities by 2045. In 2020 the construction industry was responsible for 21 percent of the total green house gas emissions in Sweden. Hence, it has become of interest to investigate new methods of mitigating the environmental impact of new buildings. One alternative for such a method is parametric design, which enables effective evaluation of multiple design solutions. This thesis investigates how a parametric design tool can be utilized in the design of load-bearing structures in order to reduce the material usage, and thus the environmental footprint. The investigation is performed by implementing a tool with the aim of producing a first draft of an optimized load-bearing structure for a timber industrial building. The tool is developed in Grasshopper with Python scripting and the results are displayed in Rhinoceros 3D. Sizing optimization combined with topology optimization are the chosen optimization methods that are integrated in the tool. The outcome of the thesis indicates the possibility of a significant reduction of material usage in the loadbearing structures of two reference projects. In conclusion, the usage of parametric tools in the construction industry could be a valuable asset in the work towards reaching net zero emissions by 2045. Moreover, the implemented tool can be an encouragement to structural engineers in the construction industry to challenge today’s way of building in order to design more sustainable buildings in the future.
Keywords: Parametric design; Sizing optimization; Topology Optimization; Timber industrial building; Glulam; Carbon dioxide equivalents; Sustainable buildings; Grasshopper; Galapagos; Rhinoceros 3D